Sesudah suboh - P. Ramlee, Tan Sri, 1928-1973 ([S.l.] : Merdeka Film Production [production company] ; Kuala Lumpur : Equity Master Sdn. Bhd. [distributor])
Sebuah kisah hidup yang paling mengharu dan mengkagumkan.
Editor, Johari Ibrahim ; music, P. Ramlee
Keywords: Love in motion pictures; Women in motion pictures